Beyond the typodont: deliberate practice, experiential learning, and feedback in postgraduate orthodontic education - Ali Borzabadi-Farahani (Frontiers in Medicine, 2026)
Background Postgraduate orthodontic education has evolved substantially, but marked global variation remains in program structure, assessment, and graduate preparedness. Feedback is central to clinical training, yet evidence specific to orthodontic education remains limited. Objective Guided by Bordage’s educational conceptual frameworks, this review explores contemporary postgraduate orthodontic education, focusing on instructional approaches, workplace-based assessments (WBAs), and trainee perceptions of feedback through the lenses of Miller’s Pyramid of Clinical Competence, Ericsson’s Deliberate Practice theory, Kolb’s Experiential Learning, and van de Ridder’s feedback models. Methods A narrative review was conducted using PubMed, Scopus, and Google Scholar for studies published up to 15 June 2026, with an updated search conducted prior to publication of the final version. Evidence ( n = 88) was synthesized thematically across five domains. Results International guidelines recommend at least 36 months of full-time orthodontic training with extensive supervised clinical experience, although substantial variation exists internationally. WBAs with timely feedback provide authentic assessment of clinical performance but are resource-intensive and influenced by assessor variability. Problem- and scenario-based learning support experiential learning and strengthen clinical reasoning beyond passive knowledge acquisition. Technology-enhanced approaches, including simulation, virtual and augmented reality, haptic systems, and flipped classroom models, may support learning and deliberate practice but are not intended to replace supervised patient care. Trainees consistently value feedback that is specific, timely, and delivered by engaged supervisors. Conclusion Clinical competence develops through repeated supervised practice supported by meaningful feedback and principles of deliberate practice. Emerging technologies may enhance training but cannot substitute for direct clinical experience. Longitudinal research is needed to assess their impact on long-term competence and patient outcomes.